Review of Evolution, Global Distribution, and Ecological Roles of Macroalgae in Tropical and Subtropical Marine Ecosystems - Septria , Audya; Noval Alghifari, Muhammad; Lawoliyo, Joachim (Yayasan Siti Widhatul Faeha, 2025)
Macroalgae play a crucial ecological role in coastal ecosystems, particularly in tropical and subtropical marine environments. This study aims to review the evolution, global distribution, and ecological functions of macroalgae through a systematic literature review approach. Scientific articles from the last ten years were selected from databases such as Scopus, ScienceDirect, and Web of Science, with a focus on macroalgae diversity, taxonomy, bioactive compounds, and environmental services. Results show that macroalgae have existed since the Proterozoic era and have evolved into morphologically and genetically diverse lineages. Distribution patterns vary significantly between tropical and subtropical zones, influenced by environmental factors such as temperature, salinity, and light intensity. In mangrove and coral reef ecosystems, macroalgae demonstrate adaptive capacity and act as habitat formers, carbon sinks, and bioindicators of ecosystem health. Several genera, including Sargassum, Padina, and Caloglossa, exhibit resilience and high ecological value. Furthermore, macroalgae are rich in bioactive compounds with potential applications in pharmaceuticals, cosmetics, and biofuels. Their high biomass productivity and carbon sequestration ability, comparable to seagrasses and mangroves, highlight their strategic role in blue carbon initiatives. However, excessive macroalgae blooms, particularly in the Atlantic Sargassum belt, raise environmental and socioeconomic concerns. This review emphasizes the need for integrated coastal management strategies to optimize the ecological and economic benefits of macroalgae sustainably.